On the evaluation of algorithm fairness strategies: a use case on gender bias - Lima, Samuel de Morais; Rêgo, Alex Sandro da Cunha; Fernandes, Damires Yluska de Souza (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2026: Anais do XXII Simpósio Brasileiro de Sistemas de Informação, 2026)
Research Context: The growing use of Machine Learning (ML) techniques in the development of predictive models to support decision-making and the development of information systems, while fostering advancements, has introduced significant ethical challenges, notably the emergence of biases that may lead to unfair decisions. Scientific and/or Practical Problem: The main scientific and practical challenge addressed is the identification and mitigation of algorithmic biases that may reproduce or exacerbate discrimination against minority groups, with a specific focus on the sensitive attribute gender. Proposed Solution and/or Analysis: This study presents an experimental evaluation of different bias mitigation strategies, including the use of the EqOddsPostprocessing and Reweighing methods from AI Fairness 360 toolkit, the application of weights, and the randomization of sensitive attribute values. Fairness performance was assessed using the Equal Opportunity and Demographic Parity metrics. Related IS Theory: This research is grounded in the theory of Algorithmic Fairness, aimed at ensuring impartiality, and in the concept of SocioTechnical Bias, which acknowledges that socially embedded prejudices are reflected in the outcomes produced by ML algorithms. Research Method: An experimental evaluation was conducted on a binary classification problem using the Portuguese SATDAP dataset. The baseline model was built with the Decision Tree algorithm, chosen for interpretability. Methodology comprised five experimental scenarios designed to test mitigation strategies and assess fairness through cross-validation. Summary of Results: Findings showed that Reweighing method fostered fairer predictions according to fairness metrics, in addition to yielding a slight but notable improvement in performance metrics such as accuracy, precision, recall, and f1-score. Contributions and Impact to IS area: This research reinforces the importance of integrating ethical guidelines and bias mitigation methodologies in developing ML systems, contributing to the construction of solutions fostering predictive fairness and countering discrimination without negatively impacting predictive performance.